Silica Deposition on Polyamide 6,6 Fabrics by Hybrid Corona-Dielectric Barrier Discharge Plasma - Grinberg Francelino, Isabella (2025)
This work aims to deposit silica (SiO2) on polyamide 6,6 fabrics by hybrid corona-dielectric barrier discharge plasma at atmospheric pressure. The reactor used, developed at the Laboratory of Plasma and Processes of the Aeronautics Institute of Technology (LPP/ITA), allows the treatment of fabric surfaces by activation and plasma deposition processes, aiming, in this order, the alteration of wettability and the deposition of silica on its surface, using a silicic acid solution (Si(OH)4) as a silica precursor. The morphology of the deposited films was evaluated by scanning electron microscopy (SEM). To identify the chemical modifications generated by the plasma treatment, the untreated and treated samples were analyzed by Fourier transform infrared spectroscopy with attenuated reflectance (FTIR-ATR) and Energy Dispersive Spectroscopy (EDS). The thermal behavior of the treated and untreated samples was evaluated by Differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA). Additionally, X-ray diffraction (XRD) was also used to identify crystalline phases in the film. The results showed that plasma processing proved to be an effective technique for modifying the surface characteristics of polyamide 6,6.